Guided Play Based Pedagogical Practices At The Kindergarten Level: Evidence Of Research At The Sissala East District Of Ghana - Abdulai, Ahmed; Batimah, Joshua (Advances in Social Sciences Research Journal, 2018)
This study constitutes an investigation into the place of guided play as a pedagogical practice by early childhood teachers at the kindergarten level at the Sissala East district of the Upper West region of Ghana. Using descriptive design coupled with explanatory sequential mixed method approach, a sample of 100 teachers at the kindergarten level at the study area were sampled using the purposive and convenience sampling techniques for the purposes of the study. A researcher-developed questionnaire and interview guide (semi-structured) served as the instruments for data collection. Using descriptive and inferential statistics both quantitative and qualitative data were analysed. Results emanating from the study points to the following: there was evidence of the use of guided play as a pedagogical practice at the study area, participants of the study also used varied teaching and learning activities whiles using guided play approach. Background information of teachers with the exception of age positively influenced their use of guided play pedagogy. Challenges faced by kindergarten teachers included but not limited to; difficulty in controlling learners and lack of teaching and learning materials. The conclusion of the study was that kindergarten teachers had adequate knowledge on guided play pedagogy and used it in teaching and learning; with the exception of age, other background information of kindergarten teachers positively influenced their use of guided play pedagogy; and also, kindergarten teachers were confronted with challenges in their use of guided play pedagogy. Among some recommendations provided by the study included provision of in-service training to kindergarten teachers on how to use guided play pedagogy. Also, workshops as well as in-service training on how background information of teachers could influence their use of guided play pedagogy should be organised by the supervision team in the education directorate of the Sissala East district for kindergarten teachers. Again, in appointing head teachers for basic schools, as part of the orientation service given to them, they should be equipped on the need to encourage their kindergarten teachers to use more of the guided play pedagogy, and play based pedagogical practices should be made part of early childhood teacher training curriculum.